GIZI ATLET LARI CEPAT 100 METER PELAJAR PUTRA INDONESIA - Dwi Gunadi (Universitas Tunas Pembangunan, 2010)
Sprint one event of althletic sport competition that held for each championship. To reach the maximal effort, someone treck 100 m is so popular if to compare with the other sprint event In programe exercisemust ellowed by menu suitable, of coursefor balancing condition dan the main aim it’s to known the balancing menu for sprinted in 100 m distance. We can to known how much needing by carbohydrate, protein, vitamane and mineral in each day. The understanding by expert of nutrition that balancing menu have to content ; carbohydrate 55 – 67%, fat 20 – 30%, protein 13 -15%. The calory needed by atlet depend of age, body, weight, sex, physical activity, weather and season. Basa Metabolic Rate (BMR) is output energy by main activityat heart, respiratory and contractionof muscular. Specific Dynamic Action (SDA) the result that needed in processing digestion food at body. The specific Dynamic Action using about 10% from Basal Metabolic Rate. The sprinter 100 m distance using 3910.3 cal and including carbohydrate, fat and protein. Example :60% of carbohydrate (2346.2 cal), fat 25% (9776,0%) and protein 15% (586,5 cal), mineral and water are using too for stability maximal activity.